Percutaneous Nephrolithotomy with and without Retrograde Pyelography: Preliminary Results of a Randomized Controlled Trial - Tabibi, Ali; Akhavizadegan, Hamed; Noori Mahdavi, Kia; Najafi Semnani, Mohammad; Karbakhsh Davari, Mojgan; Niroomand, Ali Reza (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: Since the introduction of percutaneous nephrolithotomy (PNL), many modifications to entering the pyelocalyceal system have been made. One alternative is to insert a needle pointed to an opaque stone as a landmark. The aim of this study was to compare the outcomes of managing kidney calculi by PNL with and without retrograde pyelography. Materials and Methods: In this randomized controlled trial, 55 candidates for PNL with a single opaque kidney calculus in the calyx alone, the pelvis alone, or both the calyx and the pelvis were assigned into 2 groups. Twenty-seven patients underwent PNL with a ureteral catheter, and 28 patients underwent PNL without a ureteral catheter. Clinical outcomes were compared between the 2 groups using plain radiographs taken on the first day after the procedure. Results: Patients had similar distributions regarding sex, age, operative time, hospital stay, past surgical history on the kidneys, and stone size. There was a significantly greater decrease in postoperative hemoglobin level in patients having PNL with a ureteral catheter (P < .001) than in those having the procedure without a ureteral catheter. No differences were seen among patients in the 2 groups in terms of stone-free rate, and number of patients with insignificant residue, and those needing extracorporeal shock wave lithotripsy, a second PNL procedure, or transurethral lithotripsy. Conclusions: Percutaneous nephrolithotomy without ureteral catheterization has specific benefits: urine leakage is lower and there is no need to perform cystoscopy. Patients with a single kidney calculus are good candidates for PNL without previous ureteral catheter insertion.